2011
DOI: 10.36510/learnland.v5i1.535
|View full text |Cite
|
Sign up to set email alerts
|

We Feel, Therefore We Learn: The Relevance of Affective and Social Neuroscience to Education

Abstract: Recent advances in neuroscience are highlighting connections between emotion, social functioning, and decision making that have the potential to revolutionize our understanding of the role of affect in education. In particular, the neurobiological evidence suggests that the aspects of cognition that we recruit most heavily in schools, namely learning, attention, memory, decision making, and social functioning, are both profoundly affected by and subsumed within the processes of emotion; we call these aspects e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
194
0
22

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(220 citation statements)
references
References 12 publications
4
194
0
22
Order By: Relevance
“…Neuroscience research has shown that knowledge and skills are more valuable when possessed by people who can apply them in emotionally sensitive ways. 71 Cognitive science has shown that emotions influence how health professional learners identify and perceive information, and interpret and act on it. 72 Achievement emotions have been shown to influence medical students' academic performance.…”
Section: Resultsmentioning
confidence: 99%
“…Neuroscience research has shown that knowledge and skills are more valuable when possessed by people who can apply them in emotionally sensitive ways. 71 Cognitive science has shown that emotions influence how health professional learners identify and perceive information, and interpret and act on it. 72 Achievement emotions have been shown to influence medical students' academic performance.…”
Section: Resultsmentioning
confidence: 99%
“…The very large overlap between the two ellipses represents the domain of emotional thought. This simplified diagram is based on the more extensive model presented in Immordino-Yang and Damasico (2007) and Immordino-Yang (2016). the cognitive skill is negative (for example, fear), then the skill will be encumbered (this is the bad news).…”
Section: Insights From the Relationship Between Emotion And Cognitionmentioning
confidence: 99%
“…And in each case, these feelings interact with other thoughts to change the mind in characteristic ways, and to help people learn from their experiences. Put simply, what affective neuroscience is revealing is that the mind is influenced by an interdependency of the body and brain; both the body and brain are involved, therefore, in learning (Immordino-Yang & Damasio, 2007).…”
Section: Our Bodies Our Minds; Our Cultures Our Selvesmentioning
confidence: 99%
“…As he begins thinking through the solution, he is emotionally evaluating whether each cognitive step is likely to bring him closer to a useful solution, or whether it seems to be leading him astray. From a neuropsychological perspective, 100 Mary Helen Immordino-Yang the brain systems for emotion form the 'rudder' that steers his thinking toward the development and recruitment of an effective skill (Immordino-Yang & Damasio, 2007), in this case for the solving of physics problems.Through regulating and inciting attention (Posner & Rothbart, 2005), motivation, and evaluation of possible social and cognitive outcomes, emotion serves to facilitate the student's recruitment of brain networks that support the skills he is developing. Here we use the example of solving a hypothetical physics problem, but the same mechanisms would be at play in the solving of other sorts of problems too, such as in deciding how to help one's friend or how to vote in a presidential election.…”
Section: Human Nature Human Nurturementioning
confidence: 99%
See 1 more Smart Citation